Zein-caseinate composite nanoparticles for bioactive delivery using curcumin as a probe compound. (October 2018) - Xue, Jinli; Zhang, Yaqiong; Huang, Guoren; Liu, Jie; Slavin, Margaret; Yu, Liangli (Lucy)
Abstract: This research evaluated the potential of zein-caseinate composite nanoparticles (zein-CAS NPs) as a carrier for water-insoluble bioactive food factors using curcumin (CUR) as a probe compound, and assessed its in-vitro impact using the cultured Caco-2  cells. CUR-loaded zein-CAS NPs were synthesized using a low-energy liquid-liquid dispersion method, and the obtained nanoparticles had a spherical shape with an average diameter of 187.16 nm, a narrow size distribution (polydispersity index of 0.13) and a negative surface charge of −36.43 mV. High encapsulation efficiency of CUR at 95.55% and a desirable re-dispersibility in water were also achieved, and the encapsulated CUR was in an amorphous form, as examined by differential scanning calorimetry analysis. Fourier transform infrared analysis revealed that hydrogen bonding and hydrophobic attraction were the major interactions between CUR and the zein-CAS NPs. The in-vitro release profile showed a sustained release of CUR in simulated gastric and intestinal fluids up to 72 h at 37 °C, without any burst effect. Furthermore, compared with free CUR, CUR-loaded zein-CAS NPs improved the stability of CUR against UV irradiation and thermal treatment. The cellular studies showed that, compared with free CUR, CUR-loaded zein-CAS NPs with the same CUR concentration exhibited greater bioavailability. These data suggested a possible utilization of zein-CAS NPs in improving water solubility, shelf stability, bioavailability and activity of lipophilic bioactive food factors. Graphical abstract: Image 1 Highlights: CUR was successfully loaded into zein-CAS NPs. Zein-CAS NPs improved the water solubility and stability of CUR against environmental stresses. Hydrogen bonding and hydrophobic attraction were the main interactions between CUR and zein-CAS NPs. A sustained release of CUR from zein-CAS NPs was observed in gastric and intestinal fluids. Encapsulated CUR showed an enhanced toxicity, uptake and epithelial transport in Caco-2  cells.